In situ activity of a dominant P rochlorococcus ecotype ( eHL ‐ II ) from rRNA content and cell size - Yajuan Lin; Katrina Gazsi; Veronica P. Lance; Alyse A. Larkin; Jeremy W. Chandler; Erik R. Zinser; Zackary I. Johnson (Environmental Microbiology, 2013)
Summary In the open ocean genetically diverse clades of the unicellular cyanobacteria P rochlorococcus are biogeographically structured along environmental gradients, yet little is known about their in situ activity. To address this gap, here we use the numerically dominant P rochlorococcus clade e HL ‐ II (e MIT 9312) as a model organism to develop and apply a method to examine their in situ activity using r RNA content and cell size as metrics of cellular physiology. For two representative isolates ( MIT 9312 and MIT 9215) r RNA cell −1 increases linearly with specific growth rate but is anticorrelated with cell size indicated by flow cytometrically measured ( SSC ). Although each strain has a unique relationship between cellular r RNA (or cell size) and growth rate, both strains have the same strong positive correlation between r RNA cell −1 SSC −1 and growth rate. We field test this approach and observe distinct patterns of eHL ‐ II clade specific activity (r RNA cell −1 SSC −1 ) with depth that are consistent with patterns of photosynthetic rates. This molecular technique provides unique insight into the ecology of P rochlorococcus and could potentially be expanded to include other microbes to unravel the ecological and biogeochemical contributions of genetically distinct marine side scatter microbes.

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.